Tradição e modernidade na produção poética de Roberto Pontes - Silva, Fernanda Maria Diniz da (2017)
This thesis aims analyze the poetic production of Roberto Pontes onwards its relation to the tradition and the modernity. He is one of the founders of Grupo SIN de Literatura, the group will complete fifty years in 2017. As an important author of Brazilian literature, his poetry is composed by the following books: Contracanto (1968), Lições de Espaço (1971), Temporal (1976), Memória Corporal (1982), Verbo Encarnado (1996; 2014), Breve Guitarra Galega (2002); Hierba Buena/Erva Boa (2007), 50 Poemas Escolhidos pelo Autor (2010; 2014), Lições de Tempo/Lecciones de Tiempo (2012) and Os Movimentos de Cronos/Los Movimientos de Cronos (2012). Throughout this work, it is conducted a study of Pontes‟ poems, based on the Residualidade Theory, developed by him. In order to guide our research and elaborate the text, it was used the comparative method. Therefore, we will search subsidies in the theoretical corpus of the Comparative Literature, science that provides the necessary interdisciplinarity vision to the approach of the literary text and the historical, social and cultural confluences involved. From the study of the poetic author‟s work, it was possible to confirm that Roberto Pontes rebuilt literarily the poetic characteristic of the Biblical antiquity, Troubadours and the epic song, adjusting the essence of these poetic modes to the spatial and temporal context of his time, the twentieth and twenty-first century. In addition, it was verified that the metapoetry, the social poetry, the unsubmissive poetry, the experimental poetry and philosophic poetry belong to the scope of the author‟s literary production, that it has the virtue of adapting to the nature of the artistic modernity. The work in study takes place in the historical, political and cultural setting, in which it occurs the 60s generation of the Brazilian literature, set and divided into periods by Pedro Lyra, after the consolidation of the esthetic syncretism adopted in 1967-1968 by Grupo SIN de Literatura in Ceará. Lastly, it highlights that the poet‟s artistic production, born in Fortaleza, contributed significantly to the humanization of the society when it was discussed universal themes relevant to the human essence, the same ones of all times and spaces.